Typical and atypical child and adolescent development 4: Cognition, intelligence and learning - Tetzchner, Stephen von; Tetzchner, Stephen von. (Oxon: Routledge, 2023)
"This concise guide offers an accessible introduction to the development of communication and language in infancy and childhood. It integrates insights from both typical and atypical development to reveal the fundamental aspects of human growth and development, and common developmental disorders. The topic books in this series draw on international research in the field and are informed by biological, social and cultural perspectives, offering explanations of developmental phenomena with a focus on how children and adolescents at different ages actually think, feel and act. In this volume, Stephen von Tetzchner explains key topics including: Language and Communication; early development of communication; theories of communicative development; early dialogues; gestures; the development of language; language in use; child-directed language; gender differences multilingualism and language in other modalities; and language disorders. Together with a companion website that offers topic-based quizzes, lecturer PowerPoint slides and sample essay questions, Typical and Atypical Child and Adolescent Development 5 Communication and Language Development is an essential text for all students of developmental psychology, as well as those working in the fields of child development, developmental disabilities and special education"--
1. Theory and methodology -- 2. Genes, fetal development and early neurological development -- 3. Perceptual and motor development -- 4. Cognition, intelligence and learning -- 5. Communication and language development -- 6. Emotions, temperament, personality, moral, prosocial and antisocial development -- 7. Social relations, self-awareness and identity --
"Topics from Child and adolescent psychology"--Cover.
Includes bibliographical references and index.
Keywords: Child psychology; Adolescent psychology; Child development; Developmental psychology